The Development of Lesson Plan with Disaster Mitigation Material Insertion to Teach Reading Skills - Umaemah, Amroh; Hidayat, Hendi (STIT Buntet Pesantren Cirebon, 2022)
The study was intended to develop lesson plan with disaster mitigation material insertion to teach reading skills. The type of research used is Research and Development (R & D) with the ADDIE model consisting of Analysis, Design, Development Implementation and Evaluation. The data were gained through interview with 3 teachers and 3 students, document analysis, and literature review. Data analysis was conducted through data reduction, data display, and conclusion drawing. The design stage is conducted by studying the problem and need analysis. At the development stage, we compile and design prototypes by developing lesson plans and learning materials, expert validation, as well as limited scale test. The research was conducted at SMPN 5 Lemahsugih, Majalengka. The expert validation resulted in an average of 89.58. This means that the lesson plan that was developed meets valid criteria and needs to be slightly revised. Meanwhile, the percentage of student responses to the application of the lesson plan was 89.7% in the limited scale test. The score is included in the good category, which means lesson plan is practically applied in the learning instruction.